Tumor necrosis factor-α, interleukin-8 and eosinophil cationic protein as serum markers of glucocorticoid efficacy in the treatment of bronchial asthma - Ren, Jing; Sun, Yong; Li, Gang; Zhu, Xiao-Jue; Cui, Jin-Guo (Respiratory physiology & neurobiology, 2018)
•Correlations between TNF-α, ECP, IL-8 levels and BA are studied.•TNF-α, ECP, IL-8 are negatively related to lung functions in BA patients.•TNF-α, ECP, IL-8 levels are positively correlated with clinical stages of BA.•TNF-α, ECP, IL-8 level are positively correlated with severity of BA.•TNF-α, ECP, IL-8 are markers for evaluating efficacy of glucocorticoid in BA. Bronchial asthma (BA) is a common chronic respiratory disease that has exhibited a rising global incidence in recent years. Glucocorticoids are used for the treatment of BA. Emerging evidence has demonstrated the roles of tumor necrosis factor (TNF-α), interleukin-8 (IL-8) and eosinophil cationic protein (ECP) in BA. The present study investigated whether TNF-α, IL-8 and ECP were associated with the clinical stages and severity of BA and the efficacy of glucocorticoids in the treatment of BA. A total of 199 patients with BA and 174 healthy individuals were included in this study. Patients with BA underwent glucocorticoid treatment, and the TNF-α, IL-8 and ECP levels and lung functions of the subjects were measured. The correlations of the TNF-α, IL-8 and ECP levels with BA severity, clinical staging and lung functions were assessed. We investigated whether the TNF-α, IL-8 and ECP levels aided in evaluating the efficacy of using glucocorticoids for the treatment of BA. TNF-α, IL-8 and ECP exhibited high levels in patients with BA, and glucocorticoid treatment notably decreased these levels. The TNF-α, IL-8 and ECP levels were positively correlated with the clinical stages and severity of BA and negatively correlated with lung function. TNF-α, IL-8 and ECP can be used as serum markers to predict the efficacy of glucocorticoids in the treatment of BA. The key findings of this study collectively support a role for TNF-α, IL-8 and ECP in BA development, and TNF-α, IL-8 and ECP can be used as serum markers of glucocorticoid efficacy in BA.